The Narrative of Fraud: A Framing Analysis of Two Leading Malaysian Newspapers - Sahdan, Mohd Hadafi; Sharif, Zakiyah; Md. Saleh, Md. Suhaimi (2024)
This study explores how two leading Malaysian newspapers, a prominent English-language publication referred to as Newspaper A and a widely circulated Malay-language publication referred to as Newspaper B, frame fraud reporting through investigative, neutral, and sensationalist approaches, using framing theory as the analytical lens. Framing theory posits that the media influences public perceptions by emphasizing certain aspects of an issue while downplaying others. A qualitative content analysis was conducted on 94 newspaper headlines, categorized into three framing types: investigative, neutral, and sensationalist. The findings reveal significant differences in editorial strategies. While both newspapers prioritize neutral reporting, Newspaper A allocates 80% of its coverage to this frame, compared to 71% for Newspaper B. Conversely, Newspaper B demonstrates a stronger emphasis on investigative frames (14%) and sensationalist frames (20%) compared to Newspaper A (5% and 15%, respectively). These differences highlight Newspaper B's focus on engaging readers through systemic narratives and dramatic storytelling, whereas Newspaper A leans toward factual, procedural reporting. This analysis underscores the media's dual role as an informant and influencer, shaping public discourse on fraud and accountability. The findings contribute to a broader understanding of media framing in Malaysia, emphasizing the need for a balance between investigative depth and engaging narratives to foster informed citizenship and systemic accountability